THE IMPLEMENTATION OF CARBON TAX IN INDONESIA: REGULATIONS, CHALLENGES, AND ITS IMPACTS - Hermiliani Olpah; Ambarwati; Suwandi; Wiwin Alief Bachtiar; Lala Dwipa Ananda (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
Through Law No. 7 of 2021, the Indonesian government has enacted carbon tax regulations to address climate change. While seen as an environmental and revenue solution, the policy encounters challenges. The carbon tax aims to reduce emissions and promote clean energy but poses economic risks for low-income groups. Despite potential national revenue gains, it may escalate production costs and prices, impacting domestic product competitiveness globally. Utilizing literature studies, this research analyzes the challenges, regulations, and impact of the implementation of the carbon tax in Indonesia. The study underscores the importance of considering various factors, including timing, for effective implementation. Strategic timing affects the overall economy, economic structure, and societal consumption patterns. A wellthought-out approach can enhance the carbon tax's effectiveness in reducing emissions and fostering a sustainable economic transition.